Deep brain stimulation for treatment resistant obsessive compulsive disorder; an observational study with ten patients under real-life conditions - Abdelnaim, Mohamed A.; Lang-Hambauer, Verena; Hebel, Tobias; Schoisswohl, Stefan; Schecklmann, Martin; Deuter, Daniel; Schlaier, Juergen; Langguth, Berthold (Frontiers in Psychiatry, 2023)
Introduction Obsessive-compulsive disorder (OCD) affects 2–3% of the global population, causing distress in many functioning levels. Standard treatments only lead to a partial recovery, and about 10% of the patients remain treatment-resistant. Deep brain stimulation offers a treatment option for severe, therapy-refractory OCD, with a reported response of about 60%. We report a comprehensive clinical, demographic, and treatment data for patients who were treated with DBS in our institution. Methods We offered DBS to patients with severe chronic treatment resistant OCD. Severity was defined as marked impairment in functioning and treatment resistance was defined as non-response to adequate trials of medications and psychotherapy. Between 2020 and 2022, 11 patients were implanted bilaterally in the bed nucleus of stria terminalis (BNST). Patients were evaluated with YBOCS, MADRS, GAF, CGI, and WHOQOL-BREF. We performed the ratings at baseline (before surgery), after implantation before the start of the stimulation, after reaching satisfactory stimulation parameters, and at follow-up visits 3, 6, 9, and 12 months after optimized stimulation. Results One patient has retracted his consent to publish the results of his treatment, thus we are reporting the results of 10 patients (5 males, 5 females, mean age: 37 years). Out of our 10 patients, 6 have shown a clear response indicated by a YBOCS-reduction between 42 and 100 percent at last follow-up. One further patient experienced a subjectively dramatic effect on OCD symptoms, but opted afterwards to stop the stimulation. The other 3 patients showed a slight, non-significant improvement of YBOCS between 8.8 and 21.9%. The overall mean YBOCS decreased from 28.3 at baseline to 13.3 (53% reduction) at the last follow-up. The improvement of the OCD symptoms was also accompanied by an improvement of depressive symptoms, global functioning, and quality of life. Conclusion Our results suggest that BNST-DBS can be effective for treatment-resistant OCD patients, as indicated by a reduction in symptoms and an overall improvement in functioning. Despite the need for additional research to define the patients’ selection criteria, the most appropriate anatomical target, and the most effective stimulation parameters, improved patient access for this therapy should be established.